WHICH VIGOR VARIABLES CAN BE INFLUENCED BY PHOSPHATE FERTILIZATION IN MATURE Lagerstroemia indica L. TREES? - Ivasko Júnior, Severo; Bobrowski, Rogério; Lombardi, Kátia Cylene (Floresta, 2019)
The detrimental effects of the urbanization process on urban tree development provoke the search for alternatives to minimize damage and maintain benefits provided by urban forests. The present study aimed to characterize different forms of expression and increase of vigor in Lagerstroemia indica L. After measuring vegetative, physiological and blooming vigor in the 2016 growing season, liming and subsequent treatments of increasing phosphorus dosages at 50, 100, 150 and 200% of the initial soil content were applied to trees. During the 2017 growing season, we measured the vigor conditions to evaluate the effects of fertilization on the trees. For the variables branch length, average distance internodes, leaf area, width and length of flowering, the highest phosphate fertilization (200%) dosage provided the highest mean values, while the variables dark green color and chlorophyll a and b were unaffected by the treatments. In conclusion, the vegetative and flowering vigor significantly increased from fertilization, while the physiological vigor did not respond to fertilizer application, with the application of 10 mg/dm³ of P providing the highest vigor expression in L. indica.